2013
DOI: 10.1186/1755-7682-6-24
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates adherence for treatment of osteoporosis

Abstract: BackgroundOsteoporosis is a disease of bone metabolism in which bisphosphonates (BPS) are the most common medications used in its treatment, whose main objective is to reduce the risk of fractures. The aim of this study was to conduct a systematic review on BPs adherence for treatment of osteoporosis.MethodsSystematic review of articles on BPs adherence for treatment of osteoporosis, indexed on MEDLINE (via PubMed) databases, from inception of databases until January 2013. Search terms were “Adherence, Medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…Similar and even better results were observe with calcium and vitamin D supplements, with 74.6% of all those women affected by osteoporosis taking these supplements at the time of the interview, increasing to 84.1% in the case of patients with fractures, the difference again being statistically significant. Classically, it has been reported that patients affected by osteoporosis, in general, complied poorly with treatment, both with anti-resorptive drugs 7,8, , especially the bisphosphonates 12,13 , and with the anabolics 25 , and in a more fundamental way, with calcium and vitamin D supplements 26,27 . In some series it has been reported that the first thing that patients stop taking correctly is precisely calcium and vitamin D 28 , which is exactly the opposite to what we found in our study, where 84.1% of the fractured patients took calcium and vitamin D, while only 75.9% took any other drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar and even better results were observe with calcium and vitamin D supplements, with 74.6% of all those women affected by osteoporosis taking these supplements at the time of the interview, increasing to 84.1% in the case of patients with fractures, the difference again being statistically significant. Classically, it has been reported that patients affected by osteoporosis, in general, complied poorly with treatment, both with anti-resorptive drugs 7,8, , especially the bisphosphonates 12,13 , and with the anabolics 25 , and in a more fundamental way, with calcium and vitamin D supplements 26,27 . In some series it has been reported that the first thing that patients stop taking correctly is precisely calcium and vitamin D 28 , which is exactly the opposite to what we found in our study, where 84.1% of the fractured patients took calcium and vitamin D, while only 75.9% took any other drug.…”
Section: Discussionmentioning
confidence: 99%
“…One of these is that patients affected by osteoporosis and with fragility fractures are not indicated for treatment 5,6 . Another is that once indicated, the patients abandon treatment after a certain period of time, or do not follow the treatment correctly, which is to say that they have poor persistence or adherence [7][8][9][10][11][12][13] , which leads to an increase in the risk of fracture 14,15 . We carried out this study in a population of patients previously diagnosed with osteoporosis and monitored by their primary care doctors, with the aim of understanding some of their clinical characteristics and the possible differences in their adherence to treatment, depending on whether or not they have fragility fractures.…”
Section: Introductionmentioning
confidence: 99%
“…116,[127][128][129][130][131][132] These are summarised in Appendix 6, Table 49. The majority of these reviews reported on aledronic acid and risedronic acid.…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
“…Vieira et al 132 reviewed 27 mainly observational studies of bisphosphonates (alendronic acid, ibandronic acid, risedronic acid and zoledronic acid) covering a wide range of outcomes regarding adherence and associated factors. No data were pooled and a narrative summary of the included studies was reported.…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation